A Review of Published Literature Regarding Health Issues of Coastal Communities in Sabah, Malaysia - Azzeri, A; Ching, GH; Jaafar, H; Noor, MIM; Razi, NA; Then, AYH; Suhaimi, J; Kari, F; Dahlui, M (Mdpi, 2024)
Indexed by WOS/ Scopus